2017
DOI: 10.1172/jci81870
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte proliferation prevents failure in pressure overload but not volume overload

Abstract: and ClueGO (54) and significantly regulated genes (cutoff adjusted P value < 0.05) of the transcriptomes of D2-TAC mice compared with D2-Shunt mice. The analysis is based on the following databases: GO biological function, GO cellular component, GO immune system process, GO molecular function, KEGG, REACTOME, and WikiPathways using GO Term Fusion and showing pathways with a P value of less than 0.05, a Kappa score of 0.4, and a minimum of 20 genes representing at least 5% of all genes of the pathway.Statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…S-phase cardiomyocyte nuclei were readily identified by the presence of silver grains overlaying blue X-GAL reaction product ( Figure 2B). In agreement with previous studies, 15,16,18 saline-treated D2 mice had markedly elevated levels of cardiomyocyte S-phase activity when compared with saline-treated WT mice ( Figure 2C). DOX treatment resulted in a five-fold decrease in S-phase activity in the D2 mice when assessed in the acute stage.…”
Section: D2 Mice Exhibit a Progressive Improvement In Cardiac Functiosupporting
confidence: 93%
See 3 more Smart Citations
“…S-phase cardiomyocyte nuclei were readily identified by the presence of silver grains overlaying blue X-GAL reaction product ( Figure 2B). In agreement with previous studies, 15,16,18 saline-treated D2 mice had markedly elevated levels of cardiomyocyte S-phase activity when compared with saline-treated WT mice ( Figure 2C). DOX treatment resulted in a five-fold decrease in S-phase activity in the D2 mice when assessed in the acute stage.…”
Section: D2 Mice Exhibit a Progressive Improvement In Cardiac Functiosupporting
confidence: 93%
“…15 Previous studies have shown that enhanced cardiomyocyte renewal rates in D2 mice are associated with progressive structural and functional recovery following myocardial infarction, 15,17,18 cytokineinduced atrial fibrosis, 19 and chronic pressure overload. 16 Here, we show that the enhanced level of cardiomyocyte renewal in D2 mice is associated with progressive recovery from anthracycline-induced heart failure.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…The deleterious role of rapamycin stands in contrast with its beneficial effects during pressure overload in adult mice when no cardiomyocyte proliferation occurs and when it ameliorates cardiac dysfunction by blocking pathological cardiomyocyte hypertrophy (33). The adaptive role of cardiomyocyte proliferation during pressure overload is supported by the finding that myocardial overexpression of cyclin D2 promotes cardiomyocyte proliferation during TAC in adult mice, thereby upholding cardiac function and counteracting fibrosis, while at the same time limiting cardiac hypertrophy (34). We also observed in our study that the occurrence of cardiomyocyte proliferation prevented maladaptive cardiomyocyte hypertrophy, while in turn, inhibition of cardiomyocyte proliferation (due to the deletion of GATA4 or due to PTK787 treatment) led to cardiomyocyte hypertrophy and cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%